"Releasing the beast within"? Authenticity, well-being, and the Dark Tetrad. (15th January 2019) - Womick, Jake; Foltz, Ryan M.; King, Laura A.
Abstract: Two studies examined whether the well-documented link between authenticity and well-being is moderated by the Dark Tetrad (Machiavellianism, narcissism, psychopathy, and sadism). We predicted that among those high on these traits, authenticity would be less strongly associated with well-being. Study 1 ( N  = 404) and Study 2 ( N  = 415) showed that authenticity was less strongly related to well-being among those high on Dark Tetrad personality traits. In addition, Study 2 showed that the pattern of moderation was not accounted for by desirability bias. Study 2 demonstrated that the Dark Tetrad did not moderate the association between authenticity and basic need satisfaction. In both studies, at low levels of authenticity, the Dark Tetrad were associated with higher well-being. Highlights: Authenticity and well-being were positively related. The Dark Tetrad were negatively related to authenticity. For those high on Dark Tetrad, authenticity was less strongly linked to well-being. Among the inauthentic, the Dark Tetrad were positively related to well-being. For those with dark traits, inauthenticity may represent authentic functioning.